Analysis of Symbolic Meanings Used in National Clothes of Bukhara, Samarkand and Nurata (Eurasian Journal of Learning and Academic Teaching, 2023)
The article describes the history of Uzbek national clothes from ancient times, the elements of artistic decorations in it, the symbolism of the patterns and their analysis. Each region had its own costumes from ancient times. The appearance, color, and style of clothing have changed over the centuries. This can be seen in the multilayered costumes, the weaving of fabrics, the make-up of clothes, and the ornamental ornaments. In particular, this article explores men's and women's clothing in Bukhara, Samarkand and Nurata. The semantics of the patterns used in them are detailed. Each period's costume, style, and ornaments have presented their own aesthetic design.